1992
DOI: 10.7326/0003-4819-117-2-106
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Trimethoprim-Sulfamethoxazole Prophylaxis for Toxoplasmic Encephalitis in Patients with AIDS

Abstract: Low-dose trimethoprim-sulfamethoxazole (four tablets per week) appears to be effective prophylaxis against toxoplasmic encephalitis in HIV-infected patients with previous P. carinii pneumonia. A prospective, randomized, controlled study is needed to further evaluate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0
2

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(79 citation statements)
references
References 18 publications
3
74
0
2
Order By: Relevance
“…As expected on the basis of the half-lives of 23-25 hours for dapsone and 80-105 hours for pyrimethamine [28,29], serum concentrations of dapsone decreased considerably throughout the weekly dosing interval, whereas pyrimethamine levels remained relatively stable in most of the sera examined [20]. Maintenance of high serum levels may be less important for prophylaxis than for cure, as shown by the experience with weekly doses of dapsone [18] and that with intermittent doses of trimethoprim-sulfamethoxazole [6,24,30]: both regimens prevented PCP, although the dosing interval exceeded the half-life of the individual compounds severalfold. Investigators in one of the latter studies reported undetectable trough levels in the majority of patients despite prophylactic efficacy [30].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…As expected on the basis of the half-lives of 23-25 hours for dapsone and 80-105 hours for pyrimethamine [28,29], serum concentrations of dapsone decreased considerably throughout the weekly dosing interval, whereas pyrimethamine levels remained relatively stable in most of the sera examined [20]. Maintenance of high serum levels may be less important for prophylaxis than for cure, as shown by the experience with weekly doses of dapsone [18] and that with intermittent doses of trimethoprim-sulfamethoxazole [6,24,30]: both regimens prevented PCP, although the dosing interval exceeded the half-life of the individual compounds severalfold. Investigators in one of the latter studies reported undetectable trough levels in the majority of patients despite prophylactic efficacy [30].…”
Section: Discussionmentioning
confidence: 61%
“…At this time, however, it became clear that the latter lost power because of the frequent intolerance of dapsone/ pyrimethamine and subsequent switches to aerosolized pentamidine. In addition, new data suggested that dapsone/ pyrimethamine [ 10] and possibly trimethoprim-sulfamethoxazole [24] prevent toxoplasmosis. Meanwhile, administration of trimethoprim-sulfamethoxazole became the standard prophylaxis for PCP [5,6,25], and continuing the prophylactic administration of aerosolized pentamidine to patients who were seropositive for toxoplasmosis seemed unethical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarized the data from studies which were carried out in the 1990s concerning TE epidemiology, prophylaxis regimens and outcomes. Cotrimoxazole or trimethoprimsulfamethoxazole (TMP-SMZ) was the most popular regimen for TE primary prophylaxis, while Fansidar (pyrimethamine-sulfadiazine) was prescribed at the beginning of 1990 when CD4 was lower than 200 cell/mm 3 (Carr et al, 1992;Köppen et al, 1992). However, it was not recommended for the primary prophylaxis of TE because of its side-effects especially rash and allergy.…”
Section: Te During Prophylaxis Regimen Period (1990s)mentioning
confidence: 99%
“…Even though pyrimethamine was not recommended as a first-line regimen for primary prophylaxis of TE, some medical researchers considered pyrimethamine for patients who were intolerant to TMP-SMZ, especially in high risk patients with CD4 <100 cell/mm 3 (Leport et al, 1996). TMP-SMZ was the drug of choice for prophylaxis for both PCP and toxoplasmosis (Carr et al, 1992;Richards et al, 1995). Therefore, there were various regimens ranging from 1 double-strength 1 (DS) tablet twice daily to 1 DS tablet 3 times weekly (14 DS tablets to 3 DS tablets per week) have been used.…”
Section: Te During Prophylaxis Regimen Period (1990s)mentioning
confidence: 99%